A educação militar aeronáutica brasileira: um estudo sobre a origem da formação de oficiais aviadores para a FAB (1941-1950) - Bercho, Carolina Fuzaro (2017)
The aim of this research is to analyze the formation of the Officers for the Military Aviation area from the beginning of the Ministry of Aeronautics’ creation, from 1941 to 1960 at the Aeronautics School, located in Campo dos Afonsos, Rio de Janeiro. We start from the assumption that from the 1940s onwards, the developmental initiative of Getúlio Vargas's government caused the union of the Aviation Forces in Brazil from the Creation of the Ministry of Aeronautics, and, consequently, the formation necessity of military officers for The "newcomer" Brazilian Air Force. In this context, we raise the following research question: How did the initial military education of these officers occur during and after World War II? There were prerogatives for the formation of "air warriors" through which methodological perspectives? Through the analysis of the state of the art on military education, the history of the School of Aeronautics and the collection and analysis of primary sources of research, such as the student curriculum analysis sheets and the Esquadrilha Review (elaborated by the student officers themselves). Between the years of 1941 and 1960, we will observe the educational profile and the cultural scene of the official student, its uses and customs and the routine in the form of boarding school necessary for its formation. The research contributes to the History of Education, in military format, since the object of the research involves the profile of Aeronautical Military Teaching, in a training school for Officers responsible for the air defense of the country. To speak in Military Education is to speak of methods, norms, traditions and historical legacies that refer to the beginning of education in Brazil, since the traditional educational model in the training school remains the same until the present day. Primary sources located at the University of the Air Force's Teaching Memory Center in the archives of the Air Force Academy's teaching division, legislations and interviews will serve as a database for the composition of this research.